The Effectiveness of Listen-Read-Discuss (LRD) on Students’ Reading Comprehension - Hermin Kondo; Dwi Adi Nugroho; Nurul Imansari (GLENS: Global English Insights Journal, 2023)
This study aimed to assess the effectiveness of the Listen-Read-Discuss (LRD) strategy in improving students' reading comprehension at SMAN 2 Majene. A quasi-experimental design was used with a population of 277 tenth-grade students. The sample, consisting of 60 students, was selected using convenience sampling. The assessment instrument comprised 20 multiple-choice questions administered to both the experiment and control groups before and after the treatment. The results revealed that the students' average pre-test scores in the experimental group were categorized as poor, with a mean score of 44.33. However, their post-test scores significantly improved to a good level, with a mean of 73.83. Similarly, the control group showed poor pre-test scores with a mean of 44.67, but their post-test scores improved to a good level, averaging 71.83. In conclusion, the students demonstrated enhancement in reading comprehension. The significant value of the pre-test and post-test results for both groups was 0.000, which is less than 0.05. Therefore, the t-test value was smaller than 0.05, confirming that the Alternative Hypothesis (Ha) was accepted, and the Null Hypothesis (H0) was rejected, indicating a significant effect of the LRD strategy on the reading comprehension of tenth-grade students at SMAN 2 Majene.